Design and implementation of adaptive controllers for robotic manipulator using digital signal processing (DSP) chips - Teoh, Eam Khwang (2008)
The adaptive PID controller, self-tuning regulator and model reference adaptive control have been surveyed to evaluate their suitability. Based on these studies, the self-tuning regulator (STR) and the self-organising fuzzy logic controller (SOC) were chosen for real-time implementation.